2011
DOI: 10.1177/0022487110386798
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Education Effectiveness: Quality and Equity of Future Primary Teachers’ Mathematics and Mathematics Pedagogical Content Knowledge

Abstract: The effectiveness of teacher education was examined by taking two indicators into account: future teachers’ mean achievement on a paper-and-pencil test as an indicator of quality, and the variability of teacher achievement due to background characteristics as an indicator of equity. In detail, the effects of gender and language on mathematics content knowledge and mathematics pedagogical content knowledge were examined. The analyses were embedded in the International Association for the Evaluation of Education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(50 citation statements)
references
References 14 publications
3
44
0
3
Order By: Relevance
“…Thus the increase in intrinsic teaching motivations effected by in-school OTL can be regarded as part of future teachers' professional development. Presuming that it is one of the goals of initial teacher education to foster preservice teachers' motivational development, an increase in intrinsic motivation for teaching as a career can be interpreted as evidence for teacher education effectiveness (Blömeke, Suhl, & Kaiser, 2011). This is even strengthened when taking into account that research on teacher motivation has identified teachers' intrinsic motivation positively contributes to a teacher's performance in class and other outcomes (Kunter & Holzberger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the increase in intrinsic teaching motivations effected by in-school OTL can be regarded as part of future teachers' professional development. Presuming that it is one of the goals of initial teacher education to foster preservice teachers' motivational development, an increase in intrinsic motivation for teaching as a career can be interpreted as evidence for teacher education effectiveness (Blömeke, Suhl, & Kaiser, 2011). This is even strengthened when taking into account that research on teacher motivation has identified teachers' intrinsic motivation positively contributes to a teacher's performance in class and other outcomes (Kunter & Holzberger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most interesting part of the TEDS-M study was the exploration of the differences between future teachers' Mathematics content knowledge and Mathematics pedagogical content knowledge in TEDS-M countries, since in the meantime a lot of research has been published explaining these results (e.g. Blömeke, Hsieh et al, 2011;König et al, 2011;Suhl & Kaiser, 2011;Qian & Youngs, 2016).…”
Section: Teacher Education and Development Study In Mathematics (Teds-m)mentioning
confidence: 99%
“…Scientific studies on the effectiveness of teacher education and the corresponding professionalization efforts exist in the field of general (e.g. Baumert and Kunter 2006;Blömeke et al 2008;Blömeke et al 2011) and vocational (Bouley et al 2015) education. Within the current scientific literature, the professionalization standards are often the starting point for measuring competencies.…”
Section: Research-based Training Of Vet-educatorsmentioning
confidence: 99%